PEMERIKSAAN KANDUNGAN ZAT KIMIA FORMALIN PADA IKAN ASIN YANG DIJUAL DI PASAR PARIAMAN TAHUN 2018 - Yesi Maifita; Tuti Handayani (LLDIKTI Wilayah X, 2020)
Mortality due to cancer increase every year, the world heal organization states that by 2030 there will be 11.4 million deaths from cancer and more than half are developing countries. formaldehyde is one of the causes of cancer. there are still many reported food that contain formaldehyde, one of which is salted fish. The purpose of this study was to detect the presence of formaldehyde in salted fish sold on at the Pariaman City Market in 2018. The method used was quasi-experimental using a qualitative analysis approach. The result showed that 10 percent of samples are positively contained formaldehyde.